Effects of Andrographolide-Loaded Nanostructured Lipid Carriers on Growth, Feed Efficiency, and Resistance to Streptococcus agalactiae in Nile Tilapia (Oreochromis niloticus) - Warut Kengkittipat; Manoj Tukaram Kamble; Sirikorn Kitiyodom; Jakarwan Yostawonkul; Gotchagorn Sawatphakdee; Kim D. Thompson; Seema Vijay Medhe; Nopadon Pirarat (Animals)
The increasing demand for sustainable disease management in aquaculture has intensified interest in plant-based therapeutics. This study evaluated the formulation and efficacy of andrographolide-loaded nanostructured lipid carriers (AND-NLCs) in Nile tilapia (Oreochromis niloticus) challenged with Streptococcus agalactiae ENC06. AND-NLCs were prepared by the phase-inversion technique and characterized by dynamic light scattering, transmission electron microscopy (TEM), Fourier-transform infrared spectroscopy (FTIR), and in vitro release profiling. Antibacterial activity was assessed by measuring inhibition zone diameters, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC). Growth performance, feed utilization, hepatosomatic index (HSI), and disease resistance were evaluated over a 60-day feeding trial. The AND-NLCs exhibited an optimal particle size (189.6 nm), high encapsulation efficiency (90.58%), sustained release, and structural stability. Compared to the free AND and control group, AND-NLC supplementation significantly improved growth, feed efficiency, HSI, and positive allometric growth. It also enhanced survival (73.3%) and relative percent survival (RPS = 65.6%) following S. agalactiae ENC06 infection. Antibacterial efficacy and physiological responses showed positive correlations with nanoparticle characteristics. These findings suggest that AND-NLCs enhance bioavailability and therapeutic efficacy, supporting their potential as a functional dietary additive to promote growth and improve disease resistance in tilapia aquaculture.